2020
DOI: 10.47933/ijeir.744495
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Injection Moulded Polypropylene Sawdust Composite Using Response Surface Methodology and Artificial Neural Networks

Abstract: This study focuses on the optimisation of the injection moulded Polypropylene-Sawdust composite. The Polypropylene material and sawdust were mixed together to form a homogenous mixture with various percentage composition by volume as recommended by the design of experiments using the central composite design (CCD). The two screw plunger injection moulding machine was used to produce Polypropylene-Sawdust composite at various temperature. The produced composite was evaluated for its mechanical properties which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The researchers concluded that flexural modulus of the long fiber reinforced composite was more when compared one-on-one with the short fiber reinforced composite counterpart. Aliyegbenoma and Ozakpolor [118] investigated the conjoint influence of temperature, volume of material, and nature of polymer material on mechanical properties of the PP-sawdust composite using the technique of RSM. The maximum flexural strength of the composite was 88.22 MPa and the maximum flexural modulus was 2.72 GPa at a barrel temperature of 224.65 C. Clemons and Ibach [119] carefully examined the influence of fungi on mechanical properties of HDPE containing wood fibers and molded by the technique of injection molding.…”
Section: Flexural and Impact Properties Of The Injection Molded Parti...mentioning
confidence: 99%
“…The researchers concluded that flexural modulus of the long fiber reinforced composite was more when compared one-on-one with the short fiber reinforced composite counterpart. Aliyegbenoma and Ozakpolor [118] investigated the conjoint influence of temperature, volume of material, and nature of polymer material on mechanical properties of the PP-sawdust composite using the technique of RSM. The maximum flexural strength of the composite was 88.22 MPa and the maximum flexural modulus was 2.72 GPa at a barrel temperature of 224.65 C. Clemons and Ibach [119] carefully examined the influence of fungi on mechanical properties of HDPE containing wood fibers and molded by the technique of injection molding.…”
Section: Flexural and Impact Properties Of The Injection Molded Parti...mentioning
confidence: 99%